2021
DOI: 10.3390/foods10061176
|View full text |Cite
|
Sign up to set email alerts
|

Choice Drivers for Quality-Labelled Food: A Cross-Cultural Comparison on PDO Cheese

Abstract: This study aims at examining the consumers’ preferences and drivers affecting the choice of quality-labelled food products, i.e., protected designation of origin (PDO) labelled cheese. We applied the theory of planned behaviour (TPB) to analyse the purchase of Parmigiano Reggiano PDO and Comté PDO hard cheeses in Italy and France, respectively. A cross-sectional sample of 808 consumers (400 French and 408 Italian) completed a questionnaire. Structural equation modelling (SEM) indicated perceived behavioural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
4
17
0
2
Order By: Relevance
“…This theory continues to be one of the most popular socio-psychological models used to understand and predict human behaviour [28] and has been successfully applied to behavioural studies of local product consumption [14,29], wine consumption [30,31] and local wine consumption [25,26].…”
Section: Literature Review: Theory Of Planned Behaviourmentioning
confidence: 99%
“…This theory continues to be one of the most popular socio-psychological models used to understand and predict human behaviour [28] and has been successfully applied to behavioural studies of local product consumption [14,29], wine consumption [30,31] and local wine consumption [25,26].…”
Section: Literature Review: Theory Of Planned Behaviourmentioning
confidence: 99%
“…Those cities are representative of the country and are commonly used for assessing consumer behavior [18]. Given the cultural aspects related to the North African context for conducting consumer surveys [17], the data were collected by directly approaching the respondents in supermarkets, traditional markets, or streets [9]. The participants were selected based on the consumption of local terroir foods using control questions at the beginning of the interview.…”
Section: Data Collectionmentioning
confidence: 99%
“…Several studies have analyzed preferences and attitudes of consumers in the Mediterranean region toward origin-labeled food. Recently, researchers examined consumers' preferences and drivers affecting the choice of quality-labeled food products considering PDO-labeled cheese in Italy and France [9]. The authors used a questionnaire for sampling 808 consumers and found that the motivations, the perceived ability to perform the behavior, and consumers' attitudes are significant predictors of the intention to purchase PDO-labeled cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Among TPB's applied studies, factors influencing organic food consumption were contextual across territories, especially between developed and developing countries (Thi Nguyen & Dang, 2022;Rana & Paul, 2017;Wang et al, 2019). Within TPB's core concepts, the impact of attitude on behavioral intention has been verified in previous studies (Dang & Tran, 2020;Koklic et al, 2019;Menozzi et al, 2021;Thi Nguyen & Dang, 2022) as the strongest factor impacting consumers' intention towards food options (Chu, 2018;Dangi et al, 2020;Hoang et al, 2020;Nguyen et al, 2019;Pham et al, 2019;Tuu et al, 2008). Thus, the following is hypothesized: H1: Attitude towards OFF positively influences purchasing intention of OFF.…”
Section: Literature Review and Empirical Frameworkmentioning
confidence: 92%